(Invited) Percolation Carbon Nanotube Thin Film Transistors. (8th September 2020) - Shur, Michael; Park, Junsung; Zhang, Yuhui; Liu, Xueqing; Ytterdal, Trond
Abstract : Carbon Nanotube (CNT) Thin Film Transistors use the CNT mats forming a random percolating network. The conduction contacts between the individual CNTs are determined by tunneling and are strongly affected by external agents, such as gases or biological fluids. The asymmetry of the contacts to each CNT enables the rectification of electromagnetic radiation impacted on the CNT mat with giant relative changes near the percolation point. Our experimental data show that sub-THz radiation shifts the percolation point at high intensity, when the rectified radiation changes the shape of the potential barrier between the CNT in a proximity contact. We now propose to operate the CNT Thin Film Transistors near the percolation point, where the gate bias shifts the percolation point by changing the shape of the CNT contact tunneling barriers. This ensures a sharp decrease of the subthreshold current slope.